2017
DOI: 10.1021/acs.est.6b04178
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Kinetics and Self-Assembly Mechanisms of Graphene Quantum Dots in Aqueous Solutions: Cooperative Effects of pH and Electrolytes

Abstract: The cooperative effects of pH and electrolytes on the aggregation of GQDs and the aggregate morphologies are characterized. Because GQDs have an average size of 9 nm with abundant O-functionalized edges, their suspension was very stable even in a high electrolyte concentration and low pH solution. Divalent cations (Mg and Ca) excelled at aggregating the GQD nanoplates, while monovalent cations (Na and K) did not disturb the stability. For Na and K, positive linear correlations were observed between the critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 67 publications
6
85
0
Order By: Relevance
“…Nanosheet aggregation had already been suggested, without further analysis, as a possible explanation for the PL quenching in the presence of heavy-metal ions in GOQDs [32,33]. Very recently, multiple complexation has also been thoroughly characterized and discussed in GOQDs with mono-and divalent cations [47] ) and taken into account to explain the increased interaction between graphene sheets [35]. In the present case, the formation of aggregates was confirmed by DLS measurements on the UFQD solution before and after the addition of the heavy-metal ions.…”
Section: The Effect Of Heavy-metal Ions On the Transmittance Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…Nanosheet aggregation had already been suggested, without further analysis, as a possible explanation for the PL quenching in the presence of heavy-metal ions in GOQDs [32,33]. Very recently, multiple complexation has also been thoroughly characterized and discussed in GOQDs with mono-and divalent cations [47] ) and taken into account to explain the increased interaction between graphene sheets [35]. In the present case, the formation of aggregates was confirmed by DLS measurements on the UFQD solution before and after the addition of the heavy-metal ions.…”
Section: The Effect Of Heavy-metal Ions On the Transmittance Spectrummentioning
confidence: 99%
“…We can speculate that As(III) induces a different type of aggregation, in comparison with Cu 2+ and Pb 2+ , due to the different chemical reactivity and the presence in water of arsenic as oxy-compounds. In fact, as suggested by different studies [32,47], aggregation can occur either through functional groups located at the edges [46], such as the carboxyl groups (as depicted in Scheme 1), or by multiple interaction with the π states and -OH groups on the surface of nanosheets [45,49], thus giving rise to face-to-face aggregates with a different geometrical configuration (stacking). While further studies are needed to confirm this hypothesis, it should be pointed out that the different behaviour of the three ions, as regards the PL quenching and the transmittance variations, makes it possible to discriminate between the three species by using simple optical measurements.…”
Section: +mentioning
confidence: 99%
“…However, this is easily achieved by mild oxidation. Top-down methods, on the other hand, involve exfoliation and/or cutting of carbon precursors, such as graphite 83,150 , graphene 67,105 , graphene oxide 71,86 , carbon fibres 88,153 , carbon black 101 , fullerenes 92 and carbon nanotubes 68 , through the use of reducing or oxidising agents. The cutting can be achieved either by hydrothermal 13,32,67,86,94,100 , solvothermal 34,53,93,155 , microwaveassisted 68,107 or electrochemical 90,102,[104][105][106]150 (Table 3).…”
Section: Synthesis Of Quantum Dotsmentioning
confidence: 99%
“…The colloidal stability of nanoparticle suspensions offers a crucial basis for studying their environmental transformation and assessing their environmental risk. [33] The aggregation behavior of other 2D materials, such as graphene, [34,35] graphene oxide (GO), [36][37][38] black phosphorus (BP), [39] molybdenum disulfide (MoS 2 ), tungsten disulfide (WS 2 ), and hexagonal boron nitride (h-BN) [40] have been extensively studied, and the aggregation behavior of these 2D materials follows the Derjaguin-Landau-Verwey-Overbeek (DLVO) theory. Previous studies have demonstrated that the aggregation behavior of MXenes depends on the pH, ionic strength, and type of water by measuring their colloidal properties (zeta potential and hydrodynamic size), [32,41,42] which improved our understanding of the colloidal dispersibility of MXenes.…”
Section: Introductionmentioning
confidence: 99%